Cellular-based immunotherapy in Epstein-Barr virus induced nasopharyngeal cancer. (September 2018) - Lee, Andrea Zhe Ern; Tan, Louise Soo Yee; Lim, Chwee Ming
Highlights: Up to 20% NPC patients developed relapse following definitive chemo-radiotherapy. Presence of EBV-associated tumor antigens allows potential targeting using CBI. CBI reported enhanced EBV-specific antitumor immune response with some benefit. Immune priming via CBI may diminish previous acquired resistance to failed therapy. Developments of novel CBI with combination therapy may improve cancer outcomes. Abstract: Undifferentiated Nasopharyngeal carcinoma (NPC) is ubiquitously identified with the Epstein-Barr virus (EBV), making this cancer a suitable candidate for cellular-based immunotherapy (CBI) due to its expression of potentially targetable tumor-associated viral antigens. Various preclinical and clinical studies have explored the use of cytotoxic T cells (CTLs), tumor-infiltrating lymphocytes (TILs), natural killer (NK) cells, and dendritic cells (DCs) in the treatment of both refractory and locally advanced NPC with some success. Notably, immune-mediated antitumor effects were observed even in heavily pre-treated NPC patients, suggesting potential clinical benefit of CBI in this group of patients. These immune anti-tumor effects may be even more clinically evident when used as a first-line treatment, since there may not be an intense immunosuppressive environment which is typically encountered in refractory cancer patients. Additionally, CBI may exert an effect in priming the immune system and diminishing the cancer's acquired resistance to exert a more robust response to previously failed chemotherapy. Although these results are encouraging, further refinements of clinical protocols to boost anti-tumor response and benefit a larger subset of patients proved necessary. Herein, we aim to review the rational of developing CBI in EBV-induced NPC and summarize its current applications in clinical studies.